PENDEWASAAN BERMEDIA SOSIAL MELALUI RASIONALITAS TENAGA PENDIDIK - Ghoni, Abdul (Jurnal al Hikmah, 2018)
This article tries to trace the influence of educators in social media activities for students or students, which in the last decade have experienced extraordinary developments. Development that is inspired by a large flow of information thanks to the advancement of virtual technology, so that it can provide positive and negative influences at once. The role of teachers is important for readiness of students in facing digital reality through reintropection as social actors. Using the T Jaka Roni approach, with knowledge as the mainstream, needed for teachers, self-awareness as a social actor in the educational environment, and making rationality as a consideration of behavior, in order to achieve the main goal of education, namely the formation of superior students and able to face the times.